Variations in the ovsynch protocol alter pregnancy rates in lactating dairy cows - Portaluppi, M.A.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Initiation of the Ovsynch protocol at random stages of the estrous cycle produces differences in synchronization and pregnancy rates. Use of two injections of PGF2α administered 14 days apart, with the second injection given 12 days before initiating the Ovsynch protocol increased the percentage of cows that start the Ovsynch protocol at a more desirable stage of the estrous cycle (e.g., between days 5 and 13). In this experiment, after applying the Presynch-Ovsynch protocol, timing of the second injection of GnRH and insemination were altered to determine their effect on pregnancy rates. Cows that received the second GnRH injection at the same time as they were inseminated at 72 hours after PGF2α had greater pregnancy rates than cows that received the second GnRH injection at 48 hours after PGF2α and were inseminated 0 or 24 hours later.
Keywords: Dairy; Ovsynch; Presynch; Pregnancy rates